2021
DOI: 10.5539/jel.v11n1p87
|View full text |Cite
|
Sign up to set email alerts
|

“I Apology no no I Mean I Am Sorry … Please Let Me Explain That First”: Enhancing Communicative Language Competence of Thai University Students Through CEFR-Based Online Intercultural Communication

Abstract: During this COVID-19 pandemic, no one can deny the value of online communication. It has saved our lives by preventing us from going outdoors and becoming infected, while also facilitating achievement of various personal and professional goals. Online communication can also assist us with our academic goals, whether it is used to communicate with supervisors or with people from other lingua-cultural backgrounds to practice the language. This form of communication is emphasized in the Common European F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…However, the focus has primarily been given to the actual use of speech acts by EFL learners. Various studies have used the DCT and the role-play tasks to collect spoken or written data for the analysis of pragmatic competence (Huttayavilaiphan, 2022;Jalilifar, 2009;Mohebali & Salehi, 2016).…”
Section: Dct Vs Role Play Vs Naturally Occurring Datamentioning
confidence: 99%
“…However, the focus has primarily been given to the actual use of speech acts by EFL learners. Various studies have used the DCT and the role-play tasks to collect spoken or written data for the analysis of pragmatic competence (Huttayavilaiphan, 2022;Jalilifar, 2009;Mohebali & Salehi, 2016).…”
Section: Dct Vs Role Play Vs Naturally Occurring Datamentioning
confidence: 99%
“…As technology is advancing, impacting the learning inputs and activities in learning English, studies on the relevancy between applications or platforms and CEFR in providing the models of standard language mastery have been conducted. Huttayavilaiphan (2022) revealed that their local participant students perceived the CEFR-based online intercultural communication activities with the international participant volunteers positively. It boosts their confidence and communicative language competence, encompassing linguistic, sociolinguistic, and pragmatic abilities that correspond to the CEFR (2001) scales.…”
Section: Introductionmentioning
confidence: 99%